2018
DOI: 10.1038/s41419-018-1224-3
|View full text |Cite|
|
Sign up to set email alerts
|

m6A-mediated ZNF750 repression facilitates nasopharyngeal carcinoma progression

Abstract: Nasopharyngeal carcinoma (NPC) progression is regulated by genetic, epigenetic, and epitranscript modulation. As one of the epitranscript modifications, the role of N6-Methyladenosine (m6A) has not been elucidated in NPC. In the present study, we found that the poorly methylated gene ZNF750 (encoding zinc finger protein 750) was downregulated in NPC tumor tissues and cell lines. Ectopic expression of ZNF750 blocked NPC growth in vitro and in vivo. Further studies revealed that m6A modifications maintained the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 29 publications
4
61
0
Order By: Relevance
“…High expression of YTHDF1 was found to be associated with advanced stages and unfavorable prognosis in hepatocellular carcinoma (30). The key role of m 6 A RNA methylation regulators are also noted in different cancers, such as lung cancer (31), bladder cancer (32), and nasopharyngeal carcinoma (33). Recently, a research focused on the mutations and copy number variants of 10 m 6 A regulatory genes in ccRCC and found copy number variants of these regulatory genes closely correlated with pathologic stage and prognosis of patients with ccRCC (34).…”
Section: Introductionmentioning
confidence: 94%
“…High expression of YTHDF1 was found to be associated with advanced stages and unfavorable prognosis in hepatocellular carcinoma (30). The key role of m 6 A RNA methylation regulators are also noted in different cancers, such as lung cancer (31), bladder cancer (32), and nasopharyngeal carcinoma (33). Recently, a research focused on the mutations and copy number variants of 10 m 6 A regulatory genes in ccRCC and found copy number variants of these regulatory genes closely correlated with pathologic stage and prognosis of patients with ccRCC (34).…”
Section: Introductionmentioning
confidence: 94%
“…FGF14-b is primarily located in the cytoplasm, and FGF14-a can bind to DNA and is found in the nucleus [18,23]. FGF14 expression is altered in various tumors [24][25][26] and it has been suggested to regulate apoptosis and proliferation in nasopharyngeal carcinoma and colorectal cancer [26,27]. Nonetheless, the role of FGF14 in lung cancer, especially in NSCLC remains unelucidated.…”
Section: Introductionmentioning
confidence: 99%
“…METTL3 was upregulated in AML (Barbieri et al, 2017; Vu et al, 2017), bladder cancer (Cheng et al, 2019), breast cancer (Cai et al, 2018), HCC (Chen et al, 2018), and lung cancer (Liu et al, 2018). In contrast, downregulation of METTL3 in nasopharyngeal carcinoma (Zhang et al, 2018), METTL3/METTL14 in glioblastoma (Cui et al, 2017) and endometrial cancer (Liu et al, 2018), and WTAP in AML (Bansal et al, 2014) and CRC (Zhang et al, 2016) were also reported.…”
Section: Discussionmentioning
confidence: 99%